2011
DOI: 10.1111/j.2042-3306.2011.00363.x
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of bone marrow‐derived mesenchymal stem cells demonstrates improved outcome in horses with overstrain injury of the superficial digital flexor tendon

Abstract: SummaryReasons for performing study: Mesenchymal stem (progenitor; stromal) cell (MSC) therapy has gained popularity for the treatment of equine tendon injuries but without reports of long-term follow-up. Objectives: To evaluate the safety and reinjury rate of racehorses after intralesional MSC injection in a large study of naturally occurring superficial digital flexor tendinopathy and to compare these data with those published for other treatments. Methods: Safety was assessed clinically, ultrasonographicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
317
1
22

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(355 citation statements)
references
References 53 publications
15
317
1
22
Order By: Relevance
“…Adult mesenchymal stem cells most commonly are used clinically and experimentally. Although the adult mesenchymal stem cells can be derived from bone marrow, adipose, muscle, and other tissue, the most common use in tendon healing to date is the use of bone marrow stromal cells to treat equine flexor tendon injures [3,5,19,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Adult mesenchymal stem cells most commonly are used clinically and experimentally. Although the adult mesenchymal stem cells can be derived from bone marrow, adipose, muscle, and other tissue, the most common use in tendon healing to date is the use of bone marrow stromal cells to treat equine flexor tendon injures [3,5,19,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, delivery of cells is clearly more beneficial than any single or even dual biological molecule delivery strategy, which has little chance of commercialisation, given the complexity of the system. To this end, direct cell injections were pioneered, with positive results in equine patients [44,214], even with low number of cells [215][216][217]. However, direct cell injections have failed to deliver in a consistent manner in humans due to poor cell localisation [218][219][220][221], triggering an extensive investigation into the optimal cell carrier for tendon repair [1].…”
Section: Delivery Of Viable Cell Populationsmentioning
confidence: 99%
“…There are promising studies about the use of cellular therapy to treat equine tendinitis. Clinical study results, for instance, have shown significant reduction in tendinitis relapse rates after at least two-year follow up applied to animals treated with cellular therapy in comparison to those treated with conventional therapies; their relapse rate was 27% and 56%, respectively (GODWIN et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The conventional treatment options for tendinitis are basically clinical and surgical; however, the animals hardly present healing quality good enough to allow their return to competitions with the same performance they had before the injury (MARFE et al, 2012). It is common belief that the tendon is prone to inefficient healing due to the tendinous structure, which is little vascularized, relatively acellular and has limited regeneration potential (YOUNG, 2012). It is also worth highlighting the importance of type I collagen, which is the most abundant one in the healthy tendon (approximately 95% of the total collagen) and responsible for strength and elasticity.…”
Section: Introductionmentioning
confidence: 99%